Biology of endophilin and it’s role in disease - Yang, Lu-Qi; Huang, An-Fang; Xu, Wang-Dong (Frontiers in Immunology, 2023)
Endophilin is an evolutionarily conserved family of protein that involves in a range of intracellular membrane dynamics. This family consists of five isoforms, which are distributed in various tissues. Recent studies have shown that Endophilin regulates diseases pathogenesis, including neurodegenerative diseases, tumors, cardiovascular diseases, and autoimmune diseases. In vivo, it regulates different biological functions such as vesicle endocytosis, mitochondrial morphological changes, apoptosis and autophagosome formation. Functional studies confirmed the role of Endophilin in development and progression of these diseases. In this study, we have comprehensively discussed the complex function of Endophilin and how the family contributes to diseases development. It is hoped that this study will provide new ideas for targeting Endophilin in diseases.